Clinical Correlation Between Computerized Tomography Findings and Pathologic Diagnosis in Patients Surgically Treated for Complex Renal Cysts in a Colombian Tertiary Center (2019)
IntroductionRecent data have reexamined the historical rates of malignancy observed in Bosniak IIF and III cystic lesions, and this has led to an endorsement of the use of active surveillance as the standard of care for Bosniak III renal cysts by affirming that overtreatment rates for this subgroup are close to 50%. In light of this, the present study describes the correlation between imaging studies and pathologic diagnosis in patients surgically treated for complex renal cysts in Colombia.Materials and methodsThis is a retrospective, descriptive, and observational study. We analyzed the medical histories of patients who had been surgically treated for complex renal cysts between 2010 and 2018 in the urology department of a tertiary center in Bogota, Colombia. The exclusion criteria were incomplete clinical histories and absent diagnostic images or their official interpretation.ResultsOut of the 235 urological procedures performed, nine were excluded. And 6.19% (n = 14) were cases of surgically treated complex renal cysts; 38.46% were compatible with Bosniak 46.15% were Bosniak III, and 15.38% were Bosniak IV. The percentage of renal cancer as revealed by the histopathological study was 60, 66.7 and 100 for renal cysts Bosniak IIF, III, and IV, respectively; 77.7% of these confirmed oncological cases had received a diagnosis of clear cell renal carcinoma.ConclusionsIn our study, the percentage of malignancy in patients with renal cysts Bosniak IIF and III was found to be greater compared to the findings in the recent medical literature. We believe that the management offered to the population with complex renal cysts in Colombia should be tailored to the individual risk characteristics of each patient.